Beyond the Horizon of the State: Listening to offshore detention’s longue durée - Poppy de Souza (Law Text Culture, 2020)
From the ‘stop the boats’ rhetoric of Operation Sovereign Borders to #KidsoffNauru and #BringThemHere to the 2018 Migration Amendment Bill (or ‘Medevac’ bill)—legal, discursive and temporal logics of crisis are used to both defend Australia’s border regime in the name of state securitisation and appeal to humanist calls for empathy and compassion. Yet the logic of crisis both obscures the ‘long emergencies of slow violence’ (Nixon, 2011) of the settler-colonial carceral state, and renders disposable those whose lives endure beyond its shelter or under its duress. Responding this Special Issue’s call to consider the acoustics of justice, this essay aims to listen beyond crisis in response to the artwork how are you today (Manus Recording Project Collective, 2018), a collaboration between six men then detained on Manus Island, PNG, and three men in Melbourne. Parcelled out in eighty-four, ten-minute vignettes, the resulting fourteen-hour sound archive confounds expectations of what life in offshore detention might sound like. Focusing on attention, duration, and slowness, I suggest how are you today presses us to develop more sustained and situated ethics of attention—one oriented not towards empathy or compassion, but towards the more difficult, durational and justice-oriented listening (Thill 2018) needed to unsettle Australia’s settler colonial border regimes. Taken together, or heard collectively, the work invites us to listen beyond the horizon of the state to hear to the enduring-ness of life on Manus—the solitude and suffering, but also the sociality and solidarity—as well as the limits of what settler-colonial carceral logic and law can hear.